Church and cloister of the Salesiens on the Rennweg near Vienna - Prixner, Gottfried, 1746-1819 (engraver):::Creator::::::::::::; Weidmann, F. C. (Franz Carl), 1787-1867 (author):::Contributor:::::::::::: (R. Sammer; Vienna, 2020)
Color engraving of the church and cloister of the Salesian order of the Visitation of Mary, located on the Rennweg in Vienna.